HIV-associated neurocognitive disorders. Issue 3 (June 2015) - Rumbaugh, Jeffrey A.; Tyor, William
<x xml:space="preserve">Abstract</x> Summary HIV-associated neurocognitive disorders (HAND) remain an important cause of cognitive dysfunction. Current nomenclature for HAND includes HIV-associated dementia and milder forms known as asymptomatic neurocognitive impairment (ANI) and mild neurocognitive disorder (MND). ANI and MND remain highly prevalent despite combined antiretroviral therapy (cART). These mild forms of HAND must be diagnosed through neuropsychological testing. If a patient has HAND, it remains unclear whether using a cART regimen with theoretically superior CNS penetration improves the prognosis. Nevertheless, a CNS penetration effectiveness score for antiretrovirals is available. Other factors to consider when diagnosing and treating HIV infection and HAND include the HIV clade or subtype. Data suggest that HAND occurs more often in association with certain clades, and higher vigilance for cognitive dysfunction may be recommended. Finally, comorbidities, such as diseases associated with advanced age, other infections, and drug abuse, need to be considered as cofactors for cognitive dysfunction and treated accordingly.